Epidemiology of paediatric gastrointestinal colonisation by extended spectrum cephalosporin-resistant Escherichia coli and Klebsiella pneumoniae isolates in north-west Cambodia - Van Aartsen, J; Moore, C; Parry, C; Turner, P; Phot, N; Mao, S; Suy, K; Davies, T; Geiss, A; Sheppard, A; Peto, T; Day, N; et al. (BioMed Central, 2019)
Background Extended-spectrum cephalosporin resistance (ESC-R) in Escherichia coli and Klebsiella pneumoniae is a healthcare threat; high gastrointestinal carriage rates are reported from South-east Asia. Colonisation prevalence data in Cambodia are lacking. The aim of this study was to determine gastrointestinal colonisation prevalence of ESC-resistant E. coli (ESC-R-EC) and K. pneumoniae (ESC-R-KP) in Cambodian children/adolescents and associated socio-demographic risk factors; and to characterise relevant resistance genes, their genetic contexts, and the genetic relatedness of ESC-R strains using whole genome sequencing (WGS). Results Faeces and questionnaire data were obtained from individuals < 16 years in north-western Cambodia, 2012. WGS of cultured ESC-R-EC/KP was performed (Illumina). Maximum likelihood phylogenies were used to characterise relatedness of isolates; ESC-R-associated resistance genes and their genetic contexts were identified from de novo assemblies using BLASTn and automated/manual annotation. 82/148 (55%) of children/adolescents were ESC-R-EC/KP colonised; 12/148 (8%) were co-colonised with both species. Independent risk factors for colonisation were hospitalisation (OR: 3.12, 95% CI [1.52–6.38]) and intestinal parasites (OR: 3.11 [1.29–7.51]); school attendance conferred decreased risk (OR: 0.44 [0.21–0.92]. ESC-R strains were diverse; the commonest ESC-R mechanisms were blaCTX-M 1 and 9 sub-family variants. Structures flanking these genes were highly variable, and for blaCTX-M-15, − 55 and − 27 frequently involved IS26. Chromosomal blaCTX-M integration was common in E. coli. Conclusions Gastrointestinal ESC-R-EC/KP colonisation is widespread in Cambodian children/adolescents; hospital admission and intestinal parasites are independent risk factors. The genetic contexts of blaCTX-M are highly mosaic, consistent with rapid horizontal exchange. Chromosomal integration of blaCTX-M may result in stable propagation in these community-associated pathogens.